Oxidized Lipids and Lipoprotein Dysfunction in Psoriasis. Issue 4 (October 2020) - Sorokin, Alexander V.; Remaley, Alan T.; Mehta, Nehal N.
Background: Psoriasis is a chronic immune-mediated inflammatory skin disease associated with increased development of metabolic abnormalities including obesity and dyslipidemia, as well as increased cardiovascular disease (CVD) risk. Shared pathophysiological mechanisms linking psoriasis to CVD include altered immune activation, elevated chronic systemic inflammation, and lipoprotein dysfunction characterized by oxidative damage to lipids and apolipoproteins. Objective: This review aims to provide evidence-based proof for existing relationships between psoriatic inflammation, lipid oxidation, and increased CVD risk. Methods: We included review articles and original research papers, published between 1980 and 2020, using the following key words: psoriasis, oxidized lipids, oxidation, dyslipidemia, and inflammation. Results: Systemic inflammation underlying psoriasis leads to increased skin accumulation of pro-inflammatory oxidized lipids, derived from the omega-6 fatty acids, along with counteracting anti-inflammatory lipid mediators, products of the omega-3 polyunsaturated fatty acids. Imbalance in these metabolites culminates in impaired inflammation resolution and results in multisystemic biological alterations. Sustained systemic inflammation results in excessive lipid oxidation, generating proatherogenic oxidized low- and high-density lipoproteins. Together, these pathophysiological mechanisms contribute to increased CVD risk associated with psoriasis disease. Conclusion: Available anti-inflammatory treatment showed promising clinical results in treating psoriasis, although further research is warranted on managing associated dyslipidemia and establishing novel cardiometabolic markers specific for both skin and vascular pathology.